A semiempirical description of functionalized nanodiamonds with NV- color centers - Luzanov, A.V.; Zhikol, O.A.; Omelchenko, I.V.; Nizovtsev, A.P.; Kilin, S.Ya.; Puchkarchuk, A.L.; Puchkarchuk, V.A. (Functional Materials, 2016)
Possibilities of semiempirical AM1 method in descripting the nanodiamond spectral properties are investigated with the stress on the relevant functionalized systems containing nitrogen-vacancy color centers. We studied two types of functionalization - hydroxylation and fluorination of the nanodiamond surface. It is shown that only slight spectral shifts occur (batochromic shifts in case of the hydroxylation, and hypsochromic ones in case of the fluorination). The semiempirical approach demonstrates the ability to easily and simply handle nanoclusters with hundreds carbon atoms.